EFEK LAMA PAPARAN RADIASI UV-C TERHADAP KARAKTERISTIK I-V MEMBRAN KITOSAN - Erika Winasri, Putu; Rupiasih, Ni Nyoman; Sumadiyasa, Made (BULETIN FISIKA; Vol 15 No 1 (2014): BULETIN FISIKA, 2014)
An investigation of the effects of UV exposure particularly UV-C to the characteristics of the currentvoltage (I-V) of chitosan membrane 2% has been done. The electrolyte solution was NaCl with various concentration of 0.1 mM and 10 mM, time exposure 10, 20, 40 and 60 minutes, and the increasing currents from 19 -24 ?A with increment of 0.5 ?A. Transport process is done by using a model cell membrane consist of 2 chambers. The voltage difference of membrane is measured using a calomel electrode. In this study, chitosan membranes were exposure to UV radiation for 0-60 minutes. The I-V characterization is done by the current clamp method. The solution used is NaCl solution with the concentration ratio of the both chambers (C1:C2) was 0.1 mM : 0.1 mM and the given currents were from 19 -24 ?A with increment of 0.5 ?A. From the observations obtained, the I-V characteristic graphs showed Ohmic's region, it has not showed limiting current density and overlimiting current region. The I-V characteristic graphs also shows that ion transport in NaCl solution (voltage can be measured) in the chitosan membrane system occurred at a certain current value. The increased of time exposures resulted in a decrease of conductance of chitosan membrane to ions in NaCl solution.